ANALISIS PENGARUH REALISASI PENERIMAAN PAJAK MINERAL BUKAN LOGAM DAN BATUAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN KETAPANG - B61111039, WAHYUDI (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT This study entitled "Analysis of Effect of Tax Revenues Non Metallic Minerals and Rocks Against PAD in Ketapang,â€ A case study in Ketapang Regency, itâ€™s aims to determine and analyze the effectiveness, contribution (share) and tax effect of non-metal minerals and rocks to PAD (local revnue) in Ketapang Regency . This type is Â a kuantitatif Â research with using simple regression analysis, using data from DPPKAD of Ketapang Regency on reports realization Tax Non Metallic Minerals and rocks as well as the realization of Ketapang regency budget (APBD) on period 2004 to 2013. The results of the study during the 10 years observation showed that the effectiveness or the ratio between actual revenues is highly effective of targeted with average is 156.48 %. The most effective is a stone taxes 264.06 % , 98.35% zircon least . This indicates that the potential of the mineral tax in Ketapang is still potential. Tax non-metallic minerals and rocks contribute to the local tax of 3.85% per year. Highest contribution in 2012 as 9.30 % . Contributions by minerals (type/item)Â  are zircon as 40.35 % of the amount of mineral tax or 2.38% of PAD (local revenue). While the lowest contribution is Tanah Merah ( Latent ) is only 0.04 % . The results of the regression analysis , tax non-metallic minerals and rocks have a positive influence to local revenue (PAD) with the regression coefficient is 14,764X . This means that any changes in the mineral tax unit (Rp1milion) Â gave the influence of 14,764 units (Rp 14,764 milion) to PAD . The results of t-test showed that the tax nonmetallic minerals and rocks significant effect on revenue in the real level of 95%Â  (Î±=5%) . The test results of determination ( R2 ) = 0.50, meaning that the value of Y ( PAD ) in the above regression model explained 50.0 % by variavel X ( tax non-metallic minerals and rocks ) , while the rest (50,0 % ) is explained by other factors were not analyzed in this study. Keywords : Â  Tax nonmetallic minerals and rocks, PAD, Local Tax, contibution, efectivenes